An introduction to left ventricular strain. (September 2018) - Narang, Akhil; Addetia, Karima
Abstract : Purpose of review: The assessment of left ventricular function by two-dimensional (2D) transthoracic echocardiography (TTE) is conventionally performed by measuring the ejection fraction, which has been shown to have important prognostic implications. However, left ventricular ejection fraction (LVEF) has notable shortcomings, including limited reproducibility, suboptimal inter/intraobserver variability and dependence on load/volume. Furthermore, subclinical left ventricular dysfunction cannot be measured with LVEF. With the advent of left ventricular deformation (strain) analysis, a new and robust means for assessing left ventricular function has emerged. Recent findings: Contemporary research and guidelines have attempted to standardize the definition, acquisition and measurement of left ventricular strain. In addition, multiple studies have sought to establish normal values for left ventricular strain in addition to evaluating the benefits and prognostic value of strain assessment. Summary: This article reviews the definition of left ventricular strain, outlines the types of strain and reviews how strain is acquired and measured. In addition, the advantages of strain analysis over LVEF as well as the incremental prognostic value of strain are examined. We further review the challenges associated with strain imaging as well as outline the future of strain imaging.